Peritoneal pseudomyxoma of appendicular origin with pericardial location - Navarrete, Héctor; Carriquiry, Luis A.; Avellanal, Alfredo; Pérez López, Eduardo; Priario, Julio C. (Cirugía del Uruguay, 1982)
A case of pseudomysoma pe.tonei with pericardial locazation, cause the au thors to review eng literature on this condition and they attract attention about of the rel carcnomatous nature of the maiority of peudomyxomas.